Number 3 (November 1976) - W. M. Howell; A. Black (Southeastern Fishes Council Proceedings, 1976)
Status of the Watercress Darter. By W.M. Howell and A. Black, plus News Notes, 4 pp.
Keywords: fishes; Watercress Darter